Climate change induced a progressive shift of livelihood from cereal towards Khat (Chata edulis) production in eastern Ethiopia - Daniel Assefa Tofu; Kebede Wolka (Heliyon, 2023)
Global climate change affects smallholders in sub-Saharan Africa. To cope with the changing situation, farmers employ adaptation strategies such as adjusting their livelihoods. The objective of this research was to evaluate the effects of climate change on the gradual transition in livelihood from cereal production to Khat plantation in west Harareghe, Ethiopia. Data was gathered through interviews with 273 households, 8, focus groups, and 12 key informants. Descriptive statistics and an econometric model were used to analyze quantitative data, whereas content analysis with step preprocesses was utilized to analyze and report qualitative data. . The farm households responded that climatic extremes are posing severe impacts on soil fertility (80%), crop production (93%), livestock production (91%), water scarcity (92%), and adaptive capacity of the farmers (81%). As a result, about 86% of the farmers' have been putting more emphasis and progressively shifting their livelihood from cereal to Khat (Chata edulis) crop plantation. Asides from the shrinking livelihood due to climatic shocks, high market access with better price and profitability, drought and water scarcity tolerance, ability to grow in degraded land, suitability for intercropping and three to five times harvest in a year are mentioned as the blessings attracted farmers’ to shift to Khat production. To reduce susceptibility to climate change impacts, approximately 81%, 78%, and 77% of framers, respectively, used managerial (e.g., intercropping and petty trade), technological (e.g., terracing and improved crop variety), and policy-driven (i.e., productive safety net program) strategies. In addition to this, agro-ecology, yield reduction, wealth, perceived on set of rain, soil infertility, access to markets and credit, institutional participation, land size, dependency ratio, irrigation, and access to early warning systems were found to significantly influence the adoption decision of farmers in the study area. Therefore, policy makers and planners are advised to design techniques to manage climate-induced extreme episodes and produce area specific strategies capable to increase the productivity of cereal crop and livestock.